(untitled) (Journal of Engineering, 2007)
The behavior of prestressed concrete box-girder bridges has been studied under short term loading. The 20-noded isoparametric three-dimensional brick elements have been used to model the concrete in the box-girder with its two cantilever flanges. The reinforcing bars are idealized as axial members embedded within the brick elements. The behavior of concrete in compression was simulated by an elastic-plastic work hardening model followed by a perfectly plastic response, which is terminated at the onset of crushing. In tension, a smeared crack model with fixed orthogonal cracks is used with the inclusion of models for the retained post-cracking stress and reduced shear modulus. The prestressing forces in the tendons are transformed into equivalent nodal forces and by Lin’s method. The contribution of the prestressing tendon stiffness to the global stiffness matrix is considered by treating the tendon as axial member embedded within the brick element. Two types of short-term prestress losses are considered in this study. The bond-slip phenomenon at concrete-tendon is considered by reducing the tendon axial stiffness. Several examples of prestressed concrete box girders are analyzed and compared with available experimental and theoretical studies in order to demonstrate the validity and efficiency of the proposed method. Good agreements between the results are obtained.